Debarment e a declaração de inidoneidade para contratar com a administração pública: análise comparada entre o instituto brasileiro e o norte-americano - Laís Rocha Salgado (2019)
According to the classic conception prevailing in the Brazilian Administrative Law, the sanction is a necessary measure to protect the public interest from the unlawful act. The possibility of drawing substitutive agreements that seek to avert the declaration of disqualification as established by Law No. 8.666 / 1993, however, allows the penalty to be withdrawn so that a measure of a different nature may be taken in its place, in order to promote the public interest. Given this scenario, the present research aims to promote a comparative analysis between the Brazilian and the American Administrative Law regarding the political formation of Brazil and the United States, the treatment granted to the public interest by the Administrative Law of the two countries and the respective theories of the administrative contract in other to understanding how they influenced the evolution of the administrative legal regime. After such assumptions are established, the declaration of disqualification is examined comparatively with the debarment, a legal institute provided for in the United States, presenting possible contributions to the Brazilian administrative law regarding the conclusion of agreements that seek to avert the declaration of disqualification. In conclusion, it can be seen that substitutive agreements constitute a determining tool in favor of the government, which, in exchange for pure and simple punishment, can stimulate mitigation and self-cleaning measures by its contractors, thus promoting relevant improvement in its institutional policies and, consequently, in the performance of the contracts obtained by the government. The methodological resources were case study, analysis of foreign and national legislation and literature review, with consultation of books and scientific articles.